Taller movimusic para mejorar la coordinación motora en los niños de 5 años de la Institución Educativa “La Casa del Niño” - 2018 - Abanto Vera, Johana Patricia (2019)
The purpose of this work was to determine the extent to which the "movimusic" workshop improves coordination in the 5-year-old children of the Educational Institution "La Casa del Niño" -2018._x000D_ The population of the educational institution "the house of the Child" was constituted by the 5-year-old classroom "A" with a total of 21 students, which in turn will serve as a sample, therefore, this will be the control and experimental group._x000D_ The design used was "Pre-Experimental" with a single group._x000D_ The instrument that was used to measure the level of motor coordination in children was a checklist, which; It was applied before and after the "Movimusic" workshop to improve motor coordination in 5-year-old children, which consisted of 20 experiential workshops._x000D_ It was concluded that the application of the workshop significantly influenced the level of motor coordination of 5-year-old children of the Educational Institution "La Casa del Niño 2018"